Motivation increases employees’ productivity: Comparison of public and private employees in Pakistan - Mohiuddin, Zaeema Asrar (Advances in Social Sciences Research Journal, 2018)
The productive workforce is a cornerstone of any organization that facilitates to achieve the organizational goals in a competitive environment. to enhance the productivity of the employees, motivational tools are used by the managers. Motivation is considered as the driving force that enhance the workers’ productivity. The objective of the present study is to compare themotivational factors among private and public sector employees in Pakistan. To explore the research objective, the survey was conducted from the private and public sector employees of Pakistan. Using the convenient sampling technique, 220 questionnaires were distributed among the employees who work in the different industries (private and public) in Karachi. Out of 220 questionnaires, only 200 questionnaires were received for analyzing the data. The findings highlight that the employees who work in private sector are more motivated by the monetary rewards, regular feedback from the employer and career development opportunities. On the other hand, public employees enjoy more work-life balance than private employees that positively affect their productivity.